Understanding sustained adoption of conservation agriculture among smallholder farmers: insights from a sentinel site in Malawi - Innocent Pangapanga-Phiri; Ngoma, Hambulo; Thierfelder, Christian (Cambridge University Press, 2024)
Smallholder farming systems need climate-proofing and sustainable intensification practices such as conservation agriculture (CA), are promising options. However, there is a general perception that the adoption of CA systems in southern Africa is low. Sentinel sites, where CA has been promoted for a long time, offer forward-looking new insights. This paper, thus, takes a deep dive at Nkhotakota district of Malawi to understand what could have led to the success of CA promotion and subsequent perceived high adoption. We use survey data from 620 farmers, with 298 farmers sampled from treatment areas – known to have had contact with host farmers and 320 from a control group. Overall, 31% of the farmers in both groups adopted full CA over at least a 2-year period. We also find that about 57% of farmers in the treatment area adopted full CA and only 7% of farmers in the control areas. This highlights that longer-term CA promotion with dedicated extension support can enhance the uptake of CA practices. In essence, this paper offers a different perspective to the current narrative that CA systems are too complex and knowledge intensive to be adopted despite its long-term promotion and significant investments. However, there are some nuances: sustained adoption even in sentinel sites is neither 100% nor persistent over the long term. We find an appreciable adoption decay, showing large declines from highs of 57 and 7% in adoption for at least 2 years for treatment and control, respectively, to 12% in the treatment group and practically zero in the control when we condition full CA adoption to at least 7 years. This means that fewer farmers adopted CA for a longer period and suggests some dis-adoption over time even in sentinel sites. The key adoption enablers in the sentinel sites include the availability of training, dedicated longer-term extension support coupled with farmer experiential learning through demonstration plots managed by host farmers. Based on our findings, there is need to consistently promote CA using farmer-centric approaches that include peer-to-peer learning over long periods. This allows farmers time to experiment with different CA options, enable behavioral and lasting change. At policy level, there is need to build and strengthen farmer groups to facilitate easier access to inputs like leguminous crop seeds for farmers practicing CA and to offer market-smart incentives to induce initial adoption in the short term to facilitate sustained adoption.